Exercise-induced cardioprotection: Endogenous mechanisms - Starnes, J. W.; Taylor, R. P. (Medicine & Science in Sports & Exercise, 2007)
It is now well established that exercise can result in cardioprotection against ischemia-reperfusion (I-R) injury ( 2,8-10,12,13,15,17,18,26,28,40-43,45,51,60,61,65,) however, the adaptations within the heart that provide the protection are still in doubt. The cytoprotective proteins receiving the most attention to date are antioxidant enzymes and heat shock proteins. The extent of I-R injury is dependent on the interactions of several events, including energy depletion, metabolite accumulation, oxidant stress, and calcium overload. Adaptations that directly influence any of these could affect I-R outcome. Thus, the exercise-induced cardioprotective phenotype is likely to include additional cytoprotective proteins beyond antioxidant enzymes or heat shock proteins. In this review, we will consider evidence for some of these in the cytosol, mitochondria, and sarcolemma of the cardiomyocyte. We will not consider potentially important adaptations within vascular tissue or the autonomic nervous system. Results of recent studies support the hypothesis that exercise leads to cardioprotective adaptations that are unique from other forms of preconditioning against I-R injury.